Thinking-Based Learning Strategy of Ulumul Hadith for Students of Arabic Language Department of State Islamic Institute (ar) - Ade Destri Deviana; Syarifaturrahmatullah Syarifaturrahmatullah (Universitas Islam Negeri Palangka Raya, 2019)
Ulumul hadith is a science that discusses the Prophet Muhammad